Association between the Val66Met polymorphism (rs6265/G196A) of the BDNF gene and cognitive performance with SSRI use in Arab Alzheimer's disease patients - N. Abanmy; J. Alsabhan; P. Gard; G. Scutt (Elsevier, 2021)
Brain derived neutrophic factor (BDNF) is a protein and a member of the neurotrophin family of growth factors, supports the survival of existing neurons and encourages the growth and differentiation of new neurons and synapses. The BDNF gene Val66Met polymorphism (rs6265/G196A) is responsible for BDNF synthesis that impact BDNF function that includes memory and cognition.This study investigated whether the BDNF gene Val66Met polymorphism (rs6265/G196A) is associated with cognitive function changes in both Alzheimer disease (AD) patients and elderly participants. In addition the impact of SSRI use on cognition improvement will be assessed. Healthy young, middle ages (25-59 years old) and elderly (more than 60 years old) participants (140) as well as 40 AD patients of whom are both of Saudi Arabian origin were recruited. The genotyping for the association study was performed by real-time PCR using Taqman chemistry in the ABI Prism 7900HT Sequence Detection System. Both Mini-Mental Status Examination (MMSE) and Clinical Dementia Rating (CDR) were used to assess cognitive function of healthy and AD participants, respectively.The findings showed that the BDNF Val66Met genotype distributions and allele frequencies have significant association with cognitive performance in both elderly control group and AD patients. The main findings showed that carriers of GG homozygotes (Val/Val) have superior cognitive performance among AD patients and elderly control subjects. In addition the use of SSRIs in 13 AD patients and 17 elderly participants positively improved cognitive function in elderly (p > 0.001) but not in AD patients (p = 0.1).